Hyperpolarised magnetic resonance for in vivo real-time metabolic imaging. Issue 18 (27th April 2018) - Apps, Andrew; Lau, Justin; Peterzan, Mark; Neubauer, Stefan; Tyler, Damian; Rider, Oliver
Abstract : Although non-invasive perfusion and viability imaging often provide the gateway to coronary revascularisation, current non-invasive imaging methods only report the surrogate markers of inducible hypoperfusion and presence or absence of myocardial scar, rather than actually visualising areas of ischaemia and/or viable myocardium. This may lead to suboptimal revascularisation decisions. Normally respiring (viable) cardiomyocytes convert pyruvate to acetyl-CoA and CO2 /bicarbonate (via pyruvate dehydrogenase), but under ischaemic conditions characteristically shift this conversion to lactate (by lactate dehydrogenase). Imaging pyruvate metabolism thus has the potential to improve upon current imaging techniques. Using the novel hyperpolarisation technique of dynamic nuclear polarisation (DNP), the magnetic resonance signal of injected [1- 13 C]pyruvate can be transiently magnified >10 000 times over that seen in conventional MR spectroscopy, allowing the characteristic metabolic signatures of ischaemia (lactate production) and viability (CO2 /bicarbonate production) to be directly imaged. As such DNP imaging of the downstream metabolism of [1- 13 C]pyruvate could surpass the diagnostic capabilities of contemporary ischaemia and viability testing. Here we review the technique, and with brief reference to the salient biochemistry, discuss its potential applications within cardiology. These include ischaemia and viability testing, and further characterisation of the altered metabolism seen at different stages during the natural history of heart failure.